Extranodal Rosai-Dorfman disease involving paranasal sinuses, orbits and anterior cranial fossa - Sudhansu Sekhar Mishra; Souvagya Panigrahi; Kalpalata Tripathy; Niranjan Mishra; Aparna Dwibedi (Indian Journal of Neurosurgery)
Rosai-Dorfman disease (RDD) is a rare, benign pseudolymphatous condition, predominantly involving lymph nodes. Although several cases of extra-nodal involvement have been reported previously, central nervous system involvement, particularly in the absence of nodal disease is extremely rare. Extranodal large RDD presenting as a single lesion involving sino-orbital and anterior cranial fossa has rarely been described previously. We report a case of incisional biopsy proved RDD in a young lady who presented with nasal obstruction and subsequent proptosis with visual diminution. Radiography of head and paranasal sinus demonstrated a strongly enhanced, diffuse polypoid lesion filling the bilateral sinonasal cavity and orbit with extension to the anterior cranial fossa by way of splaying the bony foramina. Pre-operative low dose steroid therapy had resulted in decreased size of the mass which facilitate gross-total surgical resection. RDD was confirmed by histopathology (emperipolesis) and immuno-histochemistry (S-100 positivity). The follow-up computed tomography 3 months later showed minimal tumor residue in left parasellar region with complete sinonasal decompression.